A rubber and a method for producing the same
Patent Information
- Application Number
- CN202611382357.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-08
- Publication Date
- 2026-10-13
AI Technical Summary
该方案能够改善芳纶纤维与橡胶基体之间的界面结合,但需要经过酸处理、清洗、干燥及环氧树脂浸渍等多道工序,处理程度控制不当时可能影响纤维本体性能;同时,该方案依赖环氧树脂和端羟基液体橡胶构建界面,未在芳纶纤维表面引入能够与橡胶硫化体系产生协同作用的含硫功能基团,也未涉及芳纶纳米纤维在天然橡胶和丁苯橡胶并用体系中的预分散问题
本发明采用由α-硫辛酸与γ-氨丙基三乙氧基硅烷经酰胺化反应制得的含硫硅烷偶联剂对芳纶纳米纤维进行表面改性,在芳纶纳米纤维表面形成含硅、含硫功能界面层,改善芳纶纳米纤维的表面润湿性及其与天然橡胶、丁苯橡胶基体之间的相容性,降低界面脱粘的可能性。含硫硅烷偶联剂中的含硫结构能够与橡胶硫化体系产生协同作用,有利于在芳纶纳米纤维与橡胶基体之间形成更加稳定的界面结合,使橡胶受到外力时产生的应力能够有效传递至芳纶纳米纤维,从而提高橡胶的拉伸强度和撕裂强度。
Smart Images

Figure CN122898046A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of rubber materials technology, specifically to a rubber and its preparation method. Background Technology
[0002] Rubber materials possess excellent elasticity, impact resistance, and vibration damping properties, and are widely used in automotive parts, construction machinery, conveyor belts, and sealing products. Existing rubber materials are typically reinforced with carbon black, silica, or aramid fibers. However, increasing the amount of carbon black can easily lead to increased viscosity and dynamic heat generation in the rubber compound. While aramid fibers have high strength and modulus, their smooth surface and low chemical activity result in insufficient compatibility with matrices such as natural rubber and styrene-butadiene rubber. Direct addition to rubber compounds can easily lead to problems such as fiber entanglement, uneven dispersion, and interfacial debonding.
[0003] For example, Chinese invention patent CN103243561B, "Surface Modification Method of Aramid and its Reinforcing Natural Rubber Material and Preparation Method," discloses a technical solution that involves treating aramid fibers with a 10-30% phosphoric acid solution at 20-50°C for 0.5-3 hours, followed by impregnation of the aramid fibers with a 5-20% epoxy resin-acetone solution for 1-2 hours, and then blending the resulting modified aramid fibers with natural rubber and hydroxyl-terminated liquid rubber. This solution can improve the interfacial bonding between aramid fibers and the rubber matrix, but it requires multiple processes such as acid treatment, cleaning, drying, and epoxy resin impregnation. Improper control of the treatment degree may affect the fiber's intrinsic properties. Furthermore, this solution relies on epoxy resin and hydroxyl-terminated liquid rubber to construct the interface, failing to introduce sulfur-containing functional groups on the aramid fiber surface that can synergize with the rubber vulcanization system, and also neglecting the pre-dispersion issue of aramid nanofibers in a natural rubber and styrene-butadiene rubber blend system.
[0004] Therefore, it is necessary to provide a rubber and its preparation method, which uses a sulfur-containing silane coupling agent to modify the surface of aramid nanofibers, and pre-disperses the modified aramid nanofibers in styrene-butadiene rubber to prepare a masterbatch, thereby reducing the entanglement and agglomeration of aramid nanofibers during the mixing process, improving the interfacial bonding strength between them and the rubber matrix, and thus improving the tensile strength, tear strength and fatigue resistance of the rubber material. Summary of the Invention
[0005] In order to overcome the shortcomings of the prior art, the present invention aims to provide a rubber and a method for preparing the same. By using a sulfur-containing silane coupling agent to modify the surface of aramid nanofibers, and pre-dispersing the modified aramid nanofibers in styrene-butadiene rubber to prepare a masterbatch, the dispersion uniformity and interfacial bonding performance of aramid nanofibers in the rubber matrix are improved, and fiber entanglement, agglomeration and interfacial debonding phenomena are reduced, thereby improving the tensile strength, tear strength and fatigue resistance of the rubber material.
[0006] To achieve the above objectives, the present invention provides the following technical solution: A rubber comprising the following components by weight: 70-85 parts natural rubber, 15-30 parts styrene-butadiene rubber, 4-6 parts modified aramid nanofibers, 18-30 parts carbon black, 3-6 parts naphthenic oil, 3-5 parts zinc oxide, 1-2 parts stearic acid, 1-2 parts antioxidant, 1.2-2.0 parts sulfur, and 1.0-1.7 parts vulcanization accelerator; The modified aramid nanofibers are aramid nanofibers with a sulfur-containing silane coupling agent loaded on their surface. The sulfur-containing silane coupling agent is prepared by an amidation reaction of α-lipoic acid and γ-aminopropyltriethoxysilane.
[0007] Furthermore, the carbon black is one of N234 carbon black and N330 carbon black; the antioxidant is antioxidant 4020.
[0008] Furthermore, the vulcanization accelerator is composed of N-cyclohexyl-2-benzothiazole sulfenamide and diphenylguanidine in a mass ratio of 1:0.2 to 0.5.
[0009] Furthermore, the aramid nanofibers have an average diameter of 10–50 nm and a length of 0.5–5 μm; the amount of the sulfur-containing silane coupling agent is 5–15% of the mass of the aramid nanofibers.
[0010] Furthermore, the modified aramid nanofibers are prepared according to the following method: Step (1): Under nitrogen protection, 4.4-4.9 g of γ-aminopropyltriethoxysilane was dissolved in 30-35 mL of anhydrous dichloromethane, followed by the sequential addition of 5.03-5.12 g of α-lipoic acid and 4.82-4.91 g of N,N′-dicyclohexylcarbodiimide. The mixture was stirred at room temperature for 2-3 h. After the reaction was completed, the solid byproducts were removed by filtration, and the dichloromethane was removed from the filtrate under reduced pressure. Anhydrous toluene was added to the crude product and the solvent was removed again under reduced pressure. The toluene co-distillation operation was repeated 3 times to obtain the sulfur-containing silane coupling agent. Step (2): Add 1-2g of aramid nanofibers to 80-120mL of an ethanol-deionized water mixture with a volume ratio of 4:1, and ultrasonically disperse at 200-400W for 20-40min to obtain an aramid nanofiber dispersion; according to the ratio of sulfur-containing silane coupling agent to 5-15% of the aramid nanofiber mass, add the sulfur-containing silane coupling agent obtained in step (1) to a mixture of 20-30 parts of ethanol and 2-3 parts of deionized water, and adjust the pH to 1mol / L hydrochloric acid. 4-5, hydrolyze at room temperature for 0.5-1.5 h to obtain a sulfur-containing silane coupling agent hydrolysate; add the sulfur-containing silane coupling agent hydrolysate dropwise to the aramid nanofiber dispersion, controlling the dropwise addition time to be 20-40 min; after the dropwise addition is complete, adjust the pH of the system to 7-8 with 5% ammonia water, and stir the reaction at 60-70℃ for 6-9 h; after the reaction is completed, centrifuge, wash three times with ethanol, and then vacuum dry at 55-65℃ for 12-16 h to obtain modified aramid nanofibers. The sulfur-containing silane coupling agent is prepared by amidation reaction of α-lipoic acid and γ-aminopropyltriethoxysilane, and its molecule simultaneously contains siloxane groups, amide groups and 1,2-dithioheterocyclopentyl groups. After hydrolysis, the siloxane groups can form a sulfur-containing functionalized interface on the surface of aramid nanofibers, and the 1,2-dithioheterocyclopentyl groups are beneficial to produce a synergistic effect with the rubber vulcanization system during the vulcanization process.
[0011] Furthermore, it includes the following steps: S1. Put styrene-butadiene rubber into a mixer for plasticizing, add modified aramid nanofibers, mix evenly at 80-100℃, control the discharge temperature not to exceed 105℃, discharge the rubber and cool to room temperature to obtain modified aramid nanofiber-styrene-butadiene rubber masterbatch. S2. Natural rubber is put into an internal mixer and plasticized for 2-4 minutes at a rotor speed of 50-70 r / min and a temperature of 60-80℃. The modified aramid nanofiber-styrene-butadiene rubber masterbatch obtained in step S1 is added and mixed for 2-3 minutes. Then, zinc oxide, stearic acid, antioxidant and half the mass of carbon black are added in sequence and mixed for 2-3 minutes. The remaining carbon black and naphthenic oil are added and mixed for 3-5 minutes. The mixing temperature is controlled at 100-120℃ and the discharge temperature is not higher than 125℃. After discharge, the mixture is cooled to below 50℃ to obtain a first-stage compound. S3. The first section of the compounded rubber is fed into a two-roll mill, sulfur and vulcanization accelerator are added, and it is mixed at 40-60°C for 5-8 minutes. After sheeting, it is left to stand for 8-24 hours, and then vulcanized to obtain the rubber. In this invention, modified aramid nanofibers are first dispersed in styrene-butadiene rubber to form a masterbatch, which is then mixed with natural rubber. This can reduce the possibility of entanglement and agglomeration when aramid nanofibers are directly added to natural rubber. The functionalized interface formed by the sulfur-containing silane coupling agent can improve the compatibility between aramid nanofibers and the rubber matrix and produce a synergistic effect with the vulcanization system. The modified aramid nanofibers and carbon black together form a multi-scale reinforcing network, thereby improving the tensile strength, tear strength and fatigue resistance of the rubber material.
[0012] Furthermore, in step S1, the rotor speed of the internal mixer is 50-70 r / min.
[0013] Furthermore, in step S3, the vulcanization temperature is 145–160°C, the vulcanization pressure is 8–15 MPa, and the vulcanization time is 8–20 min.
[0014] Compared with the prior art, the present invention has the following beneficial technical effects: This invention employs a sulfur-containing silane coupling agent, prepared by amidation reaction of α-lipoic acid and γ-aminopropyltriethoxysilane, to modify the surface of aramid nanofibers. This forms a silicon- and sulfur-containing functional interface layer on the surface of the aramid nanofibers, improving their surface wettability and compatibility with natural rubber and styrene-butadiene rubber matrices, and reducing the possibility of interfacial debonding. The sulfur-containing structure in the sulfur-containing silane coupling agent can synergistically interact with the rubber vulcanization system, facilitating the formation of a more stable interfacial bond between the aramid nanofibers and the rubber matrix. This allows the stress generated when the rubber is subjected to external forces to be effectively transferred to the aramid nanofibers, thereby improving the tensile and tear strength of the rubber.
[0015] Aramid nanofibers, with their large aspect ratio, can play a bridging, crack deflection, and crack propagation-inhibiting role in rubber matrices. Together with carbon black, they form a multi-scale reinforcing structure, improving the load-bearing capacity, tear resistance, and fatigue resistance of rubber while controlling the amount of carbon black used. This invention first mixes modified aramid nanofibers with styrene-butadiene rubber to form a masterbatch, then performs staged mixing with natural rubber and other components. This reduces the entanglement and agglomeration that occurs when aramid nanofibers are directly added to the rubber compound, resulting in a more uniform distribution within the rubber matrix and improving the stability of product performance. Attached Figure Description
[0016] Figure 1 The image shows the infrared spectrum of the modified aramid nanofibers from Example 1. Detailed Implementation
[0017] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention are described clearly and completely. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0018] The natural rubber is SCR5 standard rubber produced by Hainan Natural Rubber Industry Group Co., Ltd.; the styrene-butadiene rubber is SBR1502 produced by Sinopec Qilu Petrochemical Company; and the aramid nanofiber is a custom para-aramid nanofiber provided by Shandong Jufang New Material Co., Ltd., with a diameter of 10-50 nm and a length of 0.5-5 μm.
[0019] Example 1 This embodiment provides a rubber comprising the following raw materials in parts by weight: 70 parts natural rubber, 30 parts styrene-butadiene rubber, 4 parts modified aramid nanofibers, 18 parts N234 carbon black, 3 parts naphthenic oil, 3 parts zinc oxide, 1 part stearic acid, 1 part antioxidant 4020, 1.2 parts sulfur, and 1.0 part vulcanization accelerator; the vulcanization accelerator is composed of N-cyclohexyl-2-benzothiazole sulfenamide and diphenylguanidine in a mass ratio of 1:0.2.
[0020] The method for preparing the modified aramid nanofibers is as follows: Step (1): Under nitrogen protection, 4.4 g of γ-aminopropyltriethoxysilane was dissolved in 30 mL of anhydrous dichloromethane, and 5.03 g of α-lipoic acid and 4.82 g of N,N′-dicyclohexylcarbodiimide were added sequentially. The mixture was stirred at 25 °C for 2 h. After the reaction was completed, the solid byproduct was removed by filtration, and the dichloromethane was removed by vacuum distillation. 20 mL of anhydrous toluene was added to the crude product and the solvent was removed by vacuum distillation. The toluene co-distillation operation was repeated 3 times to obtain the sulfur-containing silane coupling agent.
[0021] Step (2): Add 1g of aramid nanofibers to 80mL of ethanol-deionized water mixture with a volume ratio of 4:1, and ultrasonically disperse at 200W for 20min; take 5% sulfur-containing silane coupling agent equivalent to the mass of aramid nanofibers, add it to a mixture of 20mL ethanol and 2mL deionized water, adjust the pH to 4 with 1mol / L hydrochloric acid, and hydrolyze at room temperature for 0.5h; add the obtained hydrolysate dropwise to the aramid nanofiber dispersion within 20min, and after the dropwise addition is complete, adjust the pH to 7 with 5% ammonia water, and react at 60℃ for 6h; centrifuge, wash 3 times with ethanol, and vacuum dry at 55℃ for 12h to obtain modified aramid nanofibers.
[0022] The method for preparing the rubber is as follows: S1. Styrene-butadiene rubber is put into an internal mixer and plasticized at a rotor speed of 50 r / min and a temperature of 80℃. Modified aramid nanofibers are added and mixed for 5 min. The discharge temperature is controlled not to exceed 105℃. The rubber is discharged and cooled to room temperature to obtain modified aramid nanofiber-styrene-butadiene rubber masterbatch. S2. Natural rubber is put into an internal mixer and plasticized for 2 minutes at a rotor speed of 50 r / min and a temperature of 60℃. Then, the masterbatch obtained in step S1 is added and mixed for 2 minutes. Zinc oxide, stearic acid, antioxidant and half the mass of carbon black N234 are added and mixed for 2 minutes. Then, the remaining carbon black N234 and naphthenic oil are added and mixed for 3 minutes. The mixing temperature is controlled at 100℃ and the discharge temperature is not higher than 125℃. After discharge, the rubber is cooled to below 50℃ to obtain a first-stage compound. S3. Put a section of mixed rubber into a two-roll mill, add sulfur and vulcanization accelerator, mix at 40°C for 5 minutes, sheet out and let stand for 8 hours, then vulcanize at 145°C and 8MPa for 8 minutes to obtain rubber.
[0023] Depend on Figure 1 It can be seen that at 3310cm -1 An absorption peak for N-H stretching vibrations appears at 1644 cm⁻¹. -1 and 1540cm -1 Absorption peaks of C=O stretching vibration in amide I and composite absorption peaks of N-H bending vibration and C-N stretching vibration in amide II were observed at 1315 cm⁻¹. -1 An absorption peak for the C-N stretching vibration in the amide III band appears at 821 cm⁻¹. -1 The presence of an out-of-plane bending vibration absorption peak of the para-substituted benzene ring near the surface indicates that the modified aramid nanofibers still retain the basic skeletal structure of aromatic polyamides.
[0024] At the same time, at 2926cm -1 and 2855cm -1 The presence of distinct aliphatic —CH2— asymmetric and symmetric stretching vibration absorption peaks at 1104 cm⁻¹ indicates that aliphatic chain structures from sulfur-containing silane coupling agents have been introduced onto the surface of the aramid nanofibers; at 1104 cm⁻¹... -1 and 1038cm -1 The presence of characteristic absorption peaks for Si—O—Si and Si—O—C stretching vibrations at 510 cm⁻¹ indicates that the siloxane groups in the hydrolyzed sulfur-containing silane coupling agent molecule are transformed into active silanol groups (-Si-OH), which undergo condensation reactions with the amide groups and trace hydroxyl groups exposed on the surface of the aramid nanofibers, forming a stable covalent and hydrogen bonded composite silicon-containing interface layer on the fiber surface; -1 The presence of a weak S-S stretching vibration absorption peak nearby can be attributed to the disulfide bond in the α-lipoic acid structure.
[0025] The presence of the intrinsic absorption peak of aramid along with the characteristic absorption peaks of aliphatic C—H, Si—O—Si, Si—O—C and S—S indicates that the sulfur-containing silane coupling agent prepared from α-lipoic acid and γ-aminopropyltriethoxysilane has been loaded onto the surface of aramid nanofibers, and the modification process has not damaged the main structure of the aramid nanofibers, proving that the modification reaction was successful.
[0026] Example 2 This embodiment provides a rubber comprising the following raw materials in parts by weight: 78 parts natural rubber, 22 parts styrene-butadiene rubber, 5 parts modified aramid nanofibers, 24 parts N330 carbon black, 4.5 parts naphthenic oil, 4 parts zinc oxide, 1.5 parts stearic acid, 1.5 parts antioxidant 4020, 1.6 parts sulfur, and 1.35 parts vulcanization accelerator; wherein the vulcanization accelerator is composed of N-cyclohexyl-2-benzothiazole sulfenamide and diphenylguanidine in a mass ratio of 1:0.35.
[0027] The method for preparing the modified aramid nanofibers is as follows: Step (1): Under nitrogen protection, 4.65 g of γ-aminopropyltriethoxysilane was dissolved in 32 mL of anhydrous dichloromethane, followed by the sequential addition of 5.08 g of α-lipoic acid and 4.86 g of N,N′-dicyclohexylcarbodiimide. The mixture was stirred at 25 °C for 2.5 h. After the reaction was completed, the solid byproducts were removed by filtration, and the dichloromethane was removed from the filtrate under reduced pressure. 20 mL of anhydrous toluene was added to the crude product, and the solvent was removed again under reduced pressure. The toluene co-distillation operation was repeated three times to remove residual water and volatile impurities, yielding a sulfur-containing silane coupling agent.
[0028] Step (2): Add 1.5g of aramid nanofibers to 100mL of a 4:1 volume ratio ethanol-deionized water mixture and ultrasonically disperse at 300W for 30min to obtain an aramid nanofiber dispersion. Weigh 0.15g of the sulfur-containing silane coupling agent obtained in step (1) and add it to a mixture of 25mL ethanol and 2.5mL deionized water. After stirring evenly, adjust the pH of the system to 4.5 with 1mol / L hydrochloric acid and hydrolyze at 25℃ for 1h to obtain a sulfur-containing silane coupling agent hydrolysate.
[0029] The obtained sulfur-containing silane coupling agent hydrolysate was added dropwise to the aramid nanofiber dispersion at a uniform rate over 30 min, with continuous stirring during the addition. After the addition was complete, the pH of the system was adjusted to 7.5 using 5% ammonia solution, and the reaction was carried out at 65℃ for 7.5 h with stirring. After the reaction was completed, the solid product was collected by centrifugation at 8000 r / min for 10 min, washed three times with ethanol, and then vacuum dried at 60℃ for 14 h to obtain modified aramid nanofibers. The above operation was repeated and the obtained products were combined until the amount of modified aramid nanofibers required for the rubber formulation was obtained.
[0030] The method for preparing the rubber is as follows: S1. Styrene-butadiene rubber is put into an internal mixer and plasticized for 2 minutes at a rotor speed of 60 r / min and a temperature of 90℃. Then, modified aramid nanofibers are added and the mixture is continued for 5 minutes to make the modified aramid nanofibers uniformly dispersed in the styrene-butadiene rubber. The discharge temperature is controlled not to exceed 105℃. The rubber is discharged and cooled to room temperature to obtain modified aramid nanofiber-styrene-butadiene rubber masterbatch. S2. Natural rubber is put into an internal mixer and plasticized for 3 minutes at a rotor speed of 60 r / min and a temperature of 70℃. The masterbatch obtained in step S1 is added and the mixture is continued to mix for 2.5 minutes. Then, zinc oxide, stearic acid, antioxidant 4020 and half the mass of carbon black N330 are added in sequence and mixed for 2.5 minutes. The remaining N330 carbon black and naphthenic oil are added and the mixture is continued to mix for 4 minutes. The mixing temperature is controlled at 110℃ and the discharge temperature is not higher than 125℃. After discharge, the mixture is naturally cooled to below 50℃ to obtain a first-stage compound. S3. The obtained section of compounded rubber is put into a two-roll mill, the roll temperature is adjusted to 50℃, sulfur and vulcanization accelerator are added in sequence, and the mixture is passed through and mixed for 6 minutes to make the sulfur and vulcanization accelerator evenly dispersed in the rubber compound. After sheeting, it is left to stand at room temperature for 16 hours, and then the rubber sheet is placed in a flat vulcanizing machine and vulcanized for 14 minutes at a vulcanization temperature of 152℃ and a vulcanization pressure of 12MPa. After cooling and demolding, the rubber is obtained.
[0031] Example 3 This embodiment provides a rubber comprising the following raw materials in parts by weight: 85 parts natural rubber, 15 parts styrene-butadiene rubber, 6 parts modified aramid nanofibers, 30 parts N234 carbon black, 6 parts naphthenic oil, 5 parts zinc oxide, 2 parts stearic acid, 2 parts antioxidant 4020, 2.0 parts sulfur, and 1.7 parts vulcanization accelerator; wherein the vulcanization accelerator is composed of N-cyclohexyl-2-benzothiazole sulfenamide and diphenylguanidine in a mass ratio of 1:0.5.
[0032] The method for preparing the modified aramid nanofibers is as follows: Step (1): Under nitrogen protection, 4.9 g of γ-aminopropyltriethoxysilane was dissolved in 35 mL of anhydrous dichloromethane, followed by the sequential addition of 5.12 g of α-lipoic acid and 4.91 g of N,N′-dicyclohexylcarbodiimide. The mixture was stirred at 25 °C for 3 h. After the reaction was completed, the solid byproducts were removed by filtration, and the dichloromethane in the filtrate was removed by vacuum distillation. 20 mL of anhydrous toluene was added to the crude product, and the solvent was removed by vacuum distillation again. The above co-distillation of toluene was repeated 3 times to remove residual water and volatile impurities, yielding a sulfur-containing silane coupling agent.
[0033] Step (2): Add 2g of aramid nanofibers to 120mL of a 4:1 volume ratio ethanol-deionized water mixture and ultrasonically disperse at 400W for 40min to obtain an aramid nanofiber dispersion. Weigh 0.30g of the sulfur-containing silane coupling agent obtained in step (1) and add it to a mixture of 30mL ethanol and 3mL deionized water. After stirring evenly, adjust the pH of the system to 5 with 1mol / L hydrochloric acid and hydrolyze at 25℃ for 1.5h to obtain a sulfur-containing silane coupling agent hydrolysate.
[0034] The obtained sulfur-containing silane coupling agent hydrolysate was added dropwise to the aramid nanofiber dispersion at a uniform rate over 40 min, with continuous stirring during the addition. After the addition was complete, the pH of the system was adjusted to 8 using 5% ammonia solution, and the reaction was carried out at 70℃ for 9 h with stirring. After the reaction was completed, the solid product was collected by centrifugation at 8000 r / min for 10 min, washed three times with ethanol, and then vacuum dried at 65℃ for 16 h to obtain modified aramid nanofibers. The above operation was repeated and the obtained products were combined until the amount of modified aramid nanofibers required for the rubber formulation was obtained.
[0035] The method for preparing the rubber is as follows: S1. Styrene-butadiene rubber is put into an internal mixer and plasticized for 2 minutes at a rotor speed of 70 r / min and a temperature of 100℃. Then, modified aramid nanofibers are added and the mixture is continued for 5 minutes to make the modified aramid nanofibers uniformly dispersed in the styrene-butadiene rubber. The discharge temperature is controlled not to exceed 105℃. The rubber is discharged and cooled to room temperature to obtain modified aramid nanofiber-styrene-butadiene rubber masterbatch. S2. Natural rubber is put into a mixer and plasticized for 4 minutes at a rotor speed of 70 r / min and a temperature of 80℃. The modified aramid nanofiber-styrene-butadiene rubber masterbatch obtained in step S1 is added and mixed for another 3 minutes. Then zinc oxide, stearic acid, antioxidant 4020 and half the mass of carbon black N234 are added in sequence and mixed for another 3 minutes. The remaining N234 carbon black and naphthenic oil are added and mixed for another 5 minutes. The mixing temperature is controlled at 120℃ and the discharge temperature is not higher than 125℃. After discharge, the rubber is naturally cooled to below 50℃ to obtain a first-stage compound. S3. The obtained section of compounded rubber is put into a two-roll mill, the roll temperature is adjusted to 60℃, sulfur and vulcanization accelerator are added in sequence, and the mixture is passed through and mixed for 8 minutes to make the sulfur and vulcanization accelerator evenly dispersed in the rubber compound. After sheeting, it is left to stand at room temperature for 24 hours, and then the rubber sheet is placed in a flat vulcanizing machine and vulcanized for 20 minutes at a vulcanization temperature of 160℃ and a vulcanization pressure of 15MPa. After cooling and demolding, the rubber is obtained.
[0036] Comparative Example 1 The difference between this comparative example and Example 3 is that 6 parts of unmodified aramid nanofibers were used to replace 6 parts of modified aramid nanofibers in equal amounts.
[0037] In step S1, 15 parts of styrene-butadiene rubber are put into an internal mixer and plasticized for 2 minutes at a rotor speed of 70 r / min and a temperature of 100℃. Then, 6 parts of unmodified aramid nanofibers are added and the mixture is continued to be mixed for 5 minutes. The discharge temperature is controlled to be no higher than 105℃. The rubber is discharged and cooled to room temperature to obtain aramid nanofiber-styrene-butadiene rubber masterbatch.
[0038] Apart from the differences mentioned above, the amounts of other raw materials and the preparation process are the same as in Example 3.
[0039] Comparative Example 2 The difference between this comparative example and Example 3 is that γ-aminopropyltriethoxysilane-modified aramid nanofibers are used to replace sulfur-containing silane coupling agent-modified aramid nanofibers in an equal amount.
[0040] The preparation method of the γ-aminopropyltriethoxysilane modified aramid nanofibers is as follows: 2g of aramid nanofibers are added to 120mL of ethanol-deionized water mixture with a volume ratio of 4:1, and ultrasonically dispersed at 400W power for 40min to obtain aramid nanofiber dispersion; 0.16g of γ-aminopropyltriethoxysilane is added to a mixture of 30mL of ethanol and 3mL of deionized water, the pH is adjusted to 5 with 1mol / L hydrochloric acid, and hydrolyzed at 25℃ for 1.5h to obtain silane hydrolysate.
[0041] The obtained silane hydrolysate was added dropwise to the aramid nanofiber dispersion at a uniform rate over 40 min. After the addition was complete, the pH was adjusted to 8 using 5% ammonia water, and the mixture was stirred at 70 °C for 9 h. After the reaction was completed, the mixture was centrifuged at 8000 r / min for 10 min, the solid product was collected, washed three times with ethanol, and then vacuum dried at 65 °C for 16 h to obtain γ-aminopropyltriethoxysilane modified aramid nanofibers.
[0042] Rubber was prepared according to steps S1 to S3 of Example 3. Except for the type of modified aramid nanofiber, the amount of other raw materials and the preparation process were the same as in Example 3.
[0043] Comparative Example 3 The difference between this comparative example and Example 3 is that the amount of modified aramid nanofibers was reduced from 6 parts to 2 parts.
[0044] This comparative example includes the following raw materials in parts by weight: 85 parts natural rubber, 15 parts styrene-butadiene rubber, 2 parts modified aramid nanofibers, 30 parts N234 carbon black, 6 parts naphthenic oil, 5 parts zinc oxide, 2 parts stearic acid, 2 parts antioxidant 4020, 2.0 parts sulfur, and 1.7 parts vulcanization accelerator.
[0045] The preparation method of the modified aramid nanofiber and the preparation process of the rubber are the same as in Example 3.
[0046] Comparative Example 4 The difference between this comparative example and Example 3 is that the amount of modified aramid nanofibers used was increased from 6 parts to 8 parts.
[0047] This comparative example includes the following raw materials in parts by weight: 85 parts natural rubber, 15 parts styrene-butadiene rubber, 8 parts modified aramid nanofibers, 30 parts N234 carbon black, 6 parts naphthenic oil, 5 parts zinc oxide, 2 parts stearic acid, 2 parts antioxidant 4020, 2.0 parts sulfur, and 1.7 parts vulcanization accelerator.
[0048] The preparation method of the modified aramid nanofiber and the preparation process of the rubber are the same as in Example 3.
[0049] Comparative Example 5 The difference between this comparative example and Example 3 is that the 30 parts of carbon black N234 are not added in two parts, but all of the carbon black N234 is added at once when zinc oxide, stearic acid and antioxidant 4020 are added.
[0050] S1. The preparation method of modified aramid nanofiber-styrene-butadiene rubber masterbatch is the same as in Example 3; S2. Add 85 parts of natural rubber to a mixer and plasticize for 4 minutes at a rotor speed of 70 r / min and a temperature of 80℃. Add the modified aramid nanofiber-styrene-butadiene rubber masterbatch obtained in step S1 and continue mixing for 3 minutes. Then add 5 parts of zinc oxide, 2 parts of stearic acid, 2 parts of antioxidant 4020 and 30 parts of carbon black N234 in sequence and mix for 3 minutes. Then add 6 parts of naphthenic oil and continue mixing for 5 minutes. Control the mixing temperature to 120℃ and the discharge temperature not to exceed 125℃. After discharge, allow it to cool naturally to below 50℃ to obtain a first-stage compound. S3. Same as in Example 3, rubber sample of Comparative Example 5 is obtained.
[0051] In this comparative example, the addition of carbon black at once will cause the viscosity of the rubber compound to rise rapidly in the early stage of internal mixing, increasing the possibility of carbon black agglomeration and uneven local dispersion.
[0052] Performance testing 1. Sample preparation and conditioning Rubber compounds obtained in Examples 1-3 and Comparative Examples 1-5 were used to prepare vulcanized sheets with a thickness of 2.0±0.2 mm according to the vulcanization conditions described in their respective embodiments. These sheets were then molded to prepare specimens for hardness, abrasion, and flexural fatigue tests. After vulcanization, each specimen was left at room temperature for at least 16 hours, and then conditioned for 24 hours in an environment of 23±2℃ and 50±5% relative humidity according to GB / T2941-2025 "General Procedures for Specimen Preparation and Conditioning in Physical Testing Methods of Rubber" before testing.
[0053] 2. Tensile properties The test was conducted according to GB / T528-2009, "Determination of Tensile Stress-Strain Properties of Vulcanized Rubber or Thermoplastic Rubber". A type 1 dumbbell-shaped specimen was used. Three points were selected on the narrow parallel section of the specimen to measure the thickness, and the median value was recorded. The gauge length was 25 mm. The specimen was clamped in an electronic universal testing machine and stretched at a speed of 500 ± 50 mm / min until fracture. The maximum tensile force and the gauge length at fracture were recorded.
[0054] 3. Tear strength The tear strength of vulcanized rubber or thermoplastic rubber was determined according to GB / T529-2008 "Determination of tear strength of vulcanized rubber or thermoplastic rubber (trouser-shaped, right-angled and crescent-shaped specimens)". A right-angled uncut specimen was used. After measuring the thickness of the tear zone, the specimen was stretched at a speed of 500±50 mm / min until it was completely torn, and the maximum tear force was recorded.
[0055] Tear strength is calculated as the ratio of maximum tear force to specimen thickness, in kN / m. Five valid specimens are tested in each group, and the median value is taken.
[0056] 4. Shore A hardness The test was conducted according to GB / T39693.4-2025, "Determination of hardness of vulcanized or thermoplastic rubber – Part 4: Determination of indentation hardness by Shore hardness tester (Shore hardness)". A Shore A hardness tester was used. The total thickness of the sample was not less than 6 mm, and the measurement position was not less than 12 mm from the edge of the sample. The reading was taken 3 seconds after the indenter foot was in complete contact with the sample. Measurements were taken at five positions on the same sample, spaced at least 6 mm apart, and the arithmetic mean was taken.
[0057] 5. Wear resistance The abrasion resistance was determined according to the non-rotating sample method in GB / T9867-2008 "Determination of Abrasion Resistance of Vulcanized Rubber or Thermoplastic Rubber (Rotating Roller Abrasion Tester Method)". The sample was prepared as a cylinder with a diameter of 16.0 ± 0.2 mm and weighed to an accuracy of 0.001 g. Under a vertical load of 10 ± 0.2 N, the sample was abraded for 40 m on the surface of P60 standard abrasion cloth. The relative volumetric abrasion loss was calculated based on the mass difference before and after abrasion, the sample density, and the mass loss of the standard reference rubber. Three samples were tested in each group, and the arithmetic mean was taken. The smaller the relative volumetric abrasion loss, the better the abrasion resistance.
[0058] 6. Flexural fatigue performance The test was conducted according to GB / T13934-2006, "Determination of Flexural Cracking and Crack Growth in Vulcanized or Thermoplastic Rubber (Demosia Type)". Demosia type specimens without artificial cuts were used, with dimensions of 150±1mm × 25±1mm × 6.3±0.2mm. The distance between the two clamps was 75mm during clamping, with a minimum distance of 19mm during flexion. The flexion frequency was 300±10 cycles / min, and the test temperature was 23±2℃. Each flexion resulted in 1×10... 4 Each time the machine is stopped for inspection, the cumulative number of flexural failures when a visible crack of not less than 2.0 mm in length first appears at the groove of the specimen is recorded as the flexural fatigue life. Five specimens are tested in each group, and the median value is taken.
[0059] Table 1: Performance Tests
[0060] As shown in Table 1, Comparative Example 1, using unmodified aramid nanofibers, exhibited a decrease in tensile strength from 27.7 MPa to 22.1 MPa, tear strength from 64.1 kN / m to 51.6 kN / m, and flexural fatigue life from 20.2 × 10⁻⁶ kN / m compared to Example 3. 4 The value dropped to 12.5 × 10⁻⁶. 4 The relative volumetric wear increased from 69 mm³ to 89 mm³. This is because the unmodified aramid nanofibers have a smooth surface, low chemical activity, and insufficient compatibility with the rubber matrix, making them prone to entanglement, agglomeration, and interfacial debonding. They cannot effectively transfer stress and prevent crack propagation, indicating the necessity of surface modification of aramid nanofibers.
[0061] Comparative Example 2 used γ-aminopropyltriethoxysilane-modified aramid nanofibers, whose tensile strength, tear strength, and flexural fatigue life were 24.5 MPa, 56.4 kN / m, and 15.7 × 10⁻⁶ kN / m, respectively. 4While superior to Comparative Example 1, this result is still significantly lower than Example 3. Ordinary aminosilanes can improve the surface wettability of aramid nanofibers but do not contain sulfur-containing structures that can synergistically interact with the rubber vulcanization system. The siloxane groups in the sulfur-containing silane coupling agent of this invention facilitate the loading of the coupling agent onto the fiber surface, while the sulfur-containing structure is beneficial for participating in the construction of the vulcanization network. This indicates that the performance improvement of this invention does not originate from ordinary silane treatment but is related to the special structure of the sulfur-containing silane coupling agent.
[0062] Comparative Example 3 reduced the amount of modified aramid nanofiber from 6 parts to 2 parts, resulting in a decrease in tensile strength, tear strength, and flexural fatigue life to 24.1 MPa, 55.2 kN / m, and 14.9 × 10⁻⁶ kN / m, respectively. 4 Next, the relative volumetric wear increased to 83mm. 3 Although its elongation at break increased to 520%, this was due to a reduction in reinforcing fibers and a decrease in the rigidity of the compound, and did not represent an improvement in overall performance. When the amount of modified aramid nanofibers is insufficient, the fibers cannot form a continuous and effective bridging reinforcement structure, and the multi-scale reinforcing network formed with carbon black is not perfect enough, thus failing to adequately prevent crack initiation and propagation.
[0063] Comparative Example 4, with the modified aramid nanofiber content increased to 8 parts, exhibited tensile strength and tear strength of 25.2 MPa and 59.0 kN / m, respectively, and a flexural fatigue life of 16.6 × 10⁻⁶. 4 In each case, the tensile strength did not continue to increase with the increase of fiber content, while the elongation at break decreased to 456% and the Shore A hardness increased to 69 degrees. This is because excessive fiber content increases the viscosity of the rubber compound and the difficulty of mixing, causing fiber entanglement and local agglomeration. Agglomeration areas are more likely to form stress concentration points. Combined with Comparative Example 3, it can be seen that controlling the modified aramid nanofiber to 4-6 parts can better balance the reinforcing effect, dispersion uniformity, and rubber compound flexibility.
[0064] Comparative Example 5, where all carbon black was added at once, exhibited tensile strength, tear strength, and flexural fatigue life of 25.6 MPa, 58.4 kN / m, and 17.3 × 10⁻⁶ kN / m, respectively. 4 The relative volumetric wear was 80 mm. 3 All of these methods are inferior to Example 3. Adding carbon black all at once will cause the viscosity of the rubber compound to rise rapidly in the early stage of mixing, increasing the possibility of carbon black agglomeration and uneven dispersion of modified aramid nanofibers. In this invention, carbon black is added in stages, and naphthenic oil is used to adjust the viscosity of the rubber compound during the second addition. This is beneficial for the uniform dispersion of carbon black and modified aramid nanofibers and the formation of a multi-scale reinforcing network, indicating that adding carbon black in stages is an important process measure to improve the strength, wear resistance and fatigue resistance of rubber.
[0065] It should be noted that, in this document, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus. Unless otherwise specified, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the process, method, article, or apparatus that includes said element.
[0066] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
[0067] Those skilled in the art should understand that the above descriptions are merely several specific embodiments of the present invention, and not all embodiments.
Claims
1. A type of rubber, characterized in that, It comprises the following components by weight: 70-85 parts natural rubber, 15-30 parts styrene-butadiene rubber, 4-6 parts modified aramid nanofibers, 18-30 parts carbon black, 3-6 parts naphthenic oil, 3-5 parts zinc oxide, 1-2 parts stearic acid, 1-2 parts antioxidant, 1.2-2.0 parts sulfur, and 1.0-1.7 parts vulcanization accelerator; The modified aramid nanofibers are aramid nanofibers with a sulfur-containing silane coupling agent loaded on their surface. The sulfur-containing silane coupling agent is prepared by an amidation reaction of α-lipoic acid and γ-aminopropyltriethoxysilane.
2. The rubber according to claim 1, characterized in that, The carbon black is one of N234 carbon black and N330 carbon black; the antioxidant is antioxidant 4020.
3. The rubber according to claim 1, characterized in that, The vulcanization accelerator is composed of N-cyclohexyl-2-benzothiazole sulfenamide and diphenylguanidine in a mass ratio of 1:0.2 to 0.
5.
4. The rubber according to claim 1, characterized in that, The aramid nanofibers have an average diameter of 10–50 nm and a length of 0.5–5 μm; the amount of the sulfur-containing silane coupling agent is 5–15% of the mass of the aramid nanofibers.
5. The rubber according to claim 1, characterized in that, The modified aramid nanofibers were prepared according to the following method: Step (1): Under nitrogen protection, 4.4-4.9 g of γ-aminopropyltriethoxysilane was dissolved in 30-35 mL of anhydrous dichloromethane, followed by the sequential addition of 5.03-5.12 g of α-lipoic acid and 4.82-4.91 g of N,N′-dicyclohexylcarbodiimide. The mixture was stirred at room temperature for 2-3 h. After the reaction was completed, the solid byproducts were removed by filtration, and the dichloromethane was removed from the filtrate under reduced pressure. Anhydrous toluene was added to the crude product and the solvent was removed again under reduced pressure. The toluene co-distillation operation was repeated 3 times to obtain the sulfur-containing silane coupling agent. Step (2): Add 1-2g of aramid nanofibers to 80-120mL of an ethanol-deionized water mixture with a volume ratio of 4:1, and ultrasonically disperse at 200-400W for 20-40min to obtain an aramid nanofiber dispersion; according to the ratio of sulfur-containing silane coupling agent to 5-15% of the aramid nanofiber mass, add the sulfur-containing silane coupling agent obtained in step (1) to a mixture of 20-30 parts of ethanol and 2-3 parts of deionized water, and adjust the pH to 1mol / L hydrochloric acid. 4-5, hydrolyze at room temperature for 0.5-1.5 h to obtain a sulfur-containing silane coupling agent hydrolysate; add the sulfur-containing silane coupling agent hydrolysate dropwise to the aramid nanofiber dispersion, controlling the dropwise addition time to be 20-40 min; after the dropwise addition is completed, adjust the pH of the system to 7-8 with 5% ammonia water by mass, and stir the reaction at 60-70℃ for 6-9 h; after the reaction is completed, centrifuge, wash three times with ethanol, and then vacuum dry at 55-65℃ for 12-16 h to obtain modified aramid nanofibers.
6. A method for preparing rubber according to any one of claims 1-5, characterized in that, Includes the following steps: S1. Put styrene-butadiene rubber into a mixer for plasticizing, add modified aramid nanofibers, mix evenly at 80-100℃, control the discharge temperature not to exceed 105℃, discharge the rubber and cool to room temperature to obtain modified aramid nanofiber-styrene-butadiene rubber masterbatch. S2. Natural rubber is put into an internal mixer and plasticized for 2-4 minutes at a rotor speed of 50-70 r / min and a temperature of 60-80℃. The modified aramid nanofiber-styrene-butadiene rubber masterbatch obtained in step S1 is added and mixed for 2-3 minutes. Then, zinc oxide, stearic acid, antioxidant and half the mass of carbon black are added in sequence and mixed for 2-3 minutes. The remaining carbon black and naphthenic oil are added and mixed for 3-5 minutes. The mixing temperature is controlled at 100-120℃ and the discharge temperature is not higher than 125℃. After discharge, the mixture is cooled to below 50℃ to obtain a first-stage compound. S3. The first section of the mixed rubber is put into a two-roll mill, sulfur and vulcanization accelerator are added, and it is mixed at 40-60°C for 5-8 minutes. After sheeting, it is left to stand for 8-24 hours and then vulcanized to obtain the rubber.
7. The method for preparing rubber according to claim 6, characterized in that, In step S1, the rotor speed of the internal mixer is 50-70 r / min.
8. The method for preparing rubber according to claim 6, characterized in that, In step S3, the vulcanization temperature is 145–160°C, the vulcanization pressure is 8–15 MPa, and the vulcanization time is 8–20 min.
Citation Information
Patent Citations
Surface modification method of aramid, and reinforced natural rubber material and preparation method thereof
CN103243561B